Mandatory Learning Of Islamic Religious Education In The Perspective Of The National Education Policy - Dedi Supriadi; Akhmad Alim; Abdu Rahmat Rosyadi (Edukasi Islami : Jurnal Pendidikan Islam, 2021)
The concept of Islamic education that are sourced from al-Quran and al-Hadith confirms that learning the religion of Islam is an obligation that absolutely needs to be done by individually obligatory (fard `ain), while the implementation and the implementation of Islamic religious education in communal (fard kifayah) be the obligation of the state, government, society and family. Research related to the compulsory learning of Islamic religious education in the perspective of the national education policy is carried out with the normative approach. The Data used is sourced from regulations and legislation as well as other provisions with data analysts conducted by descriptive-normative. The result of research and discussion can be summarized as follows: First, the Islamic religious Education must be taught in the form of subjects/courses religion in line, level and type of education, the existence of which is regulated in various laws and regulations. Islamic religious education is a core part of the curriculum of national education from primary education, secondary education and in the form of formal education, non-formal and informal. Second, in the autonomous region, the Local Government can set policy in Islamic religious education through regulation in the form of Local Regulations, Regulations of the Regional Head, and the shape of the other regulations in the held of compulsory education Islamic religious education by the institute of Islamic Education non-formal. The policy of the State or the government in Indonesia has been set in the State constitution, law, and government regulation, regulation of the Minister of Religion of Islamic religious Education became a compulsory held by each of the institutions of Islamic education and general education from basic education, secondary to higher education.